How the work models impact employee happiness and productivity in the technology companies in the post-pandemic - Sobral, Anna Vilhanna Monteiro Pereira Calmon (2024)
The Covid-19 pandemic has changed the life of global society in the past years, attempting to control the transmission of the virus. It did also affect the work models companies embraced during the period - most non-essential service companies adopted the home office, for the first time, as the new standard working model. By 2022, considering the percentage of vaccination in the world's adult population, some companies experimented with a new model of work - hybrid work, a working model that allows the employee to work both at the company and remotely. The objective of this research project is to analyse, in the post-pandemic scenario, how different companies in the technology sector are organising themselves in terms of work models, and the impacts of it on their employee's happiness and productivity. In this study, the quantitative and qualitative types of research will be used and the data collection will be from multiple sources.